Kinetic Investigation on Catalysis of Metal-Organic Framework-Type Catalyst with Nano-Sized Channels - Wu, Yun; Yang, Ben-Hong; Li, Meng; Tian, Chang-An; Qiu, Ling-Guang (Asian Journal of Chemistry, 2012)
Kinetics of oxidation of benzyl alcohol catalyzed by metal-organic frameworks (MOFs) with nano-sized channels was studied using a simple UV-VIS spectral method by choosing hydrogen peroxide as an oxidant. The effects of molar ratio of the catalyst to the substrate and the reaction temperature on the oxidation of benzyl alcohol to benzaldehyde have been investigated.